Mapping the nursing care with the NIC for patients in risk for pressure ulcer - Ana Gabriela Silva Pereira; Cássia Teixeira dos Santos; Dóris Baratz Menegon; Bruna Schroeder Mello; Fernanda Azambuja; Amália de Fátima Lucena (SciELO, 2014)
Objective:To identify the nursing care prescribed for patients in risk for pressure ulcer (PU) and to compare those with the Nursing Interventions Classification (NIC) interventions. Method: Cross mapping study conducted in a university hospital. The sample was composed of 219 adult patients hospitalized in clinical and surgical units. The inclusion criteria were: score ≤ 13 in the Braden Scale and one of the nursing diagnoses, Self-Care deficit syndrome, Impaired physical mobility, Impaired tissue integrity, Impaired skin integrity, Risk for impaired skin integrity. The data were collected retrospectively in a nursing prescription system and statistically analyzed by crossed mapping. Result: It was identified 32 different nursing cares to prevent PU, mapped in 17 different NIC interventions, within them: Skin surveillance, Pressure ulcer prevention and Positioning. Conclusion: The cross mapping showed similarities between the prescribed nursing care and the NIC interventions.